Scrutinizing Papua from Nationalism, Identity Politics, and Indonesian National Integration Perspectives - Setiarsih, Ari; Suharno, Suharno (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
This study explores theoretically the problems of Papua in the perspective of nationalism, identity politics, and national integration of Indonesia. In the context of Papua, the problems of nationalism and integration is a sensitive issue both historically and realistically. This creates a dilemmatic situation to understanding the Papuan nationalism. This article used descriptive qualitative approach with library research. The sources of data are paper that consist books, scientific journals, and mass media which gathered through documentation techniques and discourse identification. While the data analysis techniques used content analysis techniques. This study shows that: first, the emergence of aspirations about Papuan justice and independence is an attempt to maintain the autonomy, identity, and unity of Papuans, so that nationalism is a sentiment and a movement. The construction of Papuan nationalism tends to be oriented towards the ethnocultural nationalism that constructed as identity politics, so that the development of Papuan identity leads to the construction of a resistant identity. Therefore, nationalism needs to be constructed through nation-building efforts. Second, political reasoning to affirm the integration of Papua and NKRI includes: (1) building a catalyst for conflict and intensive communication; (2) implementing the politics of recognition; (3) accelerated development based on local understanding and identity of indigenous Papuans; (4) changing the way the state views the Indonesian nationalism in Papua; (5) establishing the control of violence through strengthening the role of civil society.